IMPLIKASI KLAUSULA BAKU DALAM UNDANG-UDANG NO. 8 TAHUN 1999 TENTANG PERLINDUNGAN KOMSUMEN TERHADAP PELAKU USAHA DAN KONSUMEN (Jurnal De Jure Muhammadiyah Cirebon, 2024)
Law No.8 of 1999 on Consumer Protection in Indonesia aims to protect cconsumer rights and ensure fair business pratices by business. Standard clauses, as a part of the standard contract frequently used in business transactions, have siqnificant implications for both parties, business and consumers. This study aim to analyze how the standard clauses in the law affect consumer protection and the responsiblilities of business. Through qualitative analysis,it was found that standard clauses often benefit business but can disadvantage conxumers if not properly regulated. Therefore, effective law enforcement and cumsumer education are necessary to address this imbalance and ensure fairness in business transactions.Keywords: Standard Caluses, Consumer Protection, Business